Trommius’s Travelogue: Learned Memories of Erasmus and Scaliger and Scholarly Identity in the Republic of Letters - van Miert, Dirk (Early Modern Low Countries, 2017)
On the basis of the autobiography of the orthodox Calvinist minister Abraham Trommius (1633-1719), this article argues that the Republic of Letters created its own cultures of memory. The very use of the word ‘Republic’ begs the question whether there was some kind of early modern ‘state building’ at play within the networks of learned men and women. Although sentiments of religious and political alliance cannot be ruled out in the practices of learned memories, the identity arising from these cultures aimed at stressing learning, friendship and communication. Its acts of memory were localized instances of learned identity formation across borders, serving travelling students regardless of their political and confessional affiliations. This article argues that memories of learning or learned memories present a new logical, although hitherto ignored, line of research, to complement well-studied political and confessional memories. Trommius draws particular attention to Erasmus and to Joseph Scaliger and his father Julius Caesar Scaliger. The article also discusses the broader memory of these towering figures to exemplify the study of early modern learned identity formation by means of cultures of memory.